Ivabradine in heart failure patients with reduced ejection fraction and history of paroxysmal atrial fibrillation - Yu‐Sheng Lin; Jeng‐Yu Jan; Jung‐Jung Chang; Ming‐Shyan Lin; Teng‐Yao Yang; Po‐Chang Wang; Mien‐Cheng Chen (ESC Heart Failure, 2022)
Abstract Aims Ivabradine is indicated for heart failure (HF) patients with reduced ejection fraction (HFrEF), but limited data are available with regards to the use of ivabradine in those with a history of paroxysmal atrial fibrillation (AF). To assess the effect of ivabradine in HFrEF patients with paroxysmal AF, we analysed heart failure (HF) hospitalization and mortality from multiple‐centre registry database. Methods and results We conducted a multicentre observational matched cohort study, and this study enrolled patient with symptomatic HFrEF from 1 January 2015 to 31 December 2018 who had a history of paroxysmal AF in Chang Gung Memorial Hospital medical database in Taiwan. A total of 2042 patients were eligible for the study, of whom 887 were prescribed with ivabradine and 1115 were not. The primary outcome, including HF hospitalization and cardiovascular death, and individual outcome during the 12 month observation period were analysed after inverse probability of treatment weighting. The ivabradine group had significantly lower mean heart rate after 12 months follow‐up than the non‐ivabradine group (P < 0.05). The primary outcome was significantly higher in the ivabradine group than the non‐ivabradine group after 12 months follow‐up (hazard ratio [HR] = 1.58; 95% confidence interval [CI], 1.26–2.00, P < 0.001). Moreover, the ivabradine group had a significantly higher event rate of HF hospitalization (HR = 1.56; 95% CI, 1.40–1.75, P < 0.001) and HF death (HR = 1.67; 95% CI, 1.14–2.44, P = 0.009) than the non‐ivabradine group. Conclusions Ivabradine treatment was associated with an increased risk of HF hospitalization in symptomatic HFrEF patients with a history of paroxysmal AF. Further prospective randomized studies are warranted.